Comprehensive Analysis of N6-Methyladenosine (m6A) Methylation in Neuromyelitis Optica Spectrum Disorders - Yang, Hong; Wu, Yi-Fan; Ding, Jie; Liu, Wei; Zhu, De-Sheng; Shen, Xia-Feng; Guan, Yang-Tai (Frontiers in Genetics, 2021)
Abstract Background: N6-Methyladenosine (m6A) methylation is the most prevalent internal posttranscriptional modification of mammalian mRNA, but its role in neuromyelitis optica spectrum disorders (NMOSDs) is not known. Aims: To explore the mechanism of m6A in NMOSD patients. Methods: This study assessed the m6A methylation levels in blood from two groups: NMOSD patients and healthy controls. Methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA-seq were performed to assess differences in m6A methylation between NMOSD patients and healthy controls. Ultra-high performance liquid chromatography coupled with triple quadruple mass spectrometry (UPLC-QQQ-MS) was performed to determine m6A levels. Differential m6A methylation genes were validated by MeRIP-qPCR. Results: Compared with that in the control group, the total m6A level was decreased in the NMOSD group. Genes with upregulated methylation were primarily enriched in processes associated with RNA splicing, mRNA processing, and innate immune response, while genes with downregulated methylation were enriched in processes associated with the regulation of transcription, DNA templating, and the positive regulation of I-kappa B kinase/NF-kappa B signalling. Conclusions: These findings demonstrate that differential m6A methylation may act on functional genes to regulate immune homeostasis in NMOSD.